Ultra-fast electro-optic switching control using a soliton pulse within a modified add-drop multiplexer - Soysouvanh, S.; Jalil, M. A.; Amiri, I. S.; Ali, J.; Singh, G.; Mitatha, S.; Yupapin, P.; Grattan, K. T.V.; Yoshida, M. (My University, 2018)
We have proposed the use of a soliton pulse that propagates within a modified add-drop filter, which is made of a GaAsInP/P material. It is in the form of a Panda-ring resonator, from which a bright/dark soliton pulse is input into a system via an input port. The conversion between bright and dark soliton pulses is introduced at the 3 dB coupler, i.e. the change in phase of π/2. But it is not superimposed each other. The output solitons obtained at the through and drop ports are bight and dark solitons respectively. Both signals can be used to form “ON’ and “OFF” or “1” and “0”, which are useful for the digital bit generation. The switching speed of the system can be improved by employing the two nonlinear side rings. In application, secure output bits can be arranged by using the alternative input solitons or the control ports, where the input bright and dark solitons can be converted into output bits. This means that the output bits can be randomly switched between “1” and “0”, which can be identified by the sender. Moreover, the additional information can be multiplexed via the add port and transmitted in either free space or optical fiber via the whispering gallery mode and through port outputs. Finally, the electro-optic switching can be transferred and the electronic switching by the embedded stacked layers, where the ultrafast switching of light input can lead the ultrafast electrical switching speed. The switching speed of ~ 5 fs and the offset time of ~ 220 fs of the “on” and OFF” are achieved by using the selected ring parameters.